PENGEMBANGAN FLIPBOOK BERBASIS PROJECT BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII SMP ISLAM SIRAJUN JADID PONTIANAK - Lobertus Sivi; Sandie; Hartono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to see the feasibility of developing project-based learning-based flipbooks on mathematical problem-solving abilities seen from validity, practicality and effectiveness. The method used is Research and Development (R&D) with an ADDIE research design. This research was carried out at Sirajun Jadid Islamic Junior High School Pontianak with a trial subject of 30 grade VII students. From the validity results, it shows that the validity of the media reaches a percentage of 89.08% and the validation of the material is a percentage of 97.73 with the criterion of